Intravitreal Dexamethasone Implant for Postoperative Macular Oedema Secondary to Vitrectomy for Epiretinal Membrane and Retinal Detachment: A Systematic Review and Meta-Analysis - Parisi, Guglielmo (J Ophthalmol, 2021)
PURPOSE: To evaluate the efficacy of intravitreal dexamethasone implant (DEX) for the treatment of macular oedema secondary to vitrectomy for epiretinal membrane (ERM) and retinal detachment (RD) by conducting a systematic review with meta-analysis of published studies. METHODS: Studies reporting clinical outcomes of DEX use for the treatment of macular oedema secondary to ERM and RD vitrectomy were searched on PubMed and Embase databases. The primary outcome was best-corrected visual acuity (BCVA) change between baseline and post-DEX treatment, reported as mean difference (MD) with 95% confidence interval (CI). Mean central macular thickness (CMT) change was assessed as a secondary outcome. Postimplant adverse events, including intraocular pressure rise and cataract development, were reported as well. RESULTS: Five uncontrolled studies, 1 nonrandomized controlled study, and 1 randomized controlled study were included, with a total of 5 cohorts and 3 cohorts in the ERM group and RD group, respectively. Considering the last available follow-up, a significant improvement in postimplant BCVA was found in the overall population, irrespective of the indication for vitrectomy (MD = −0.28, 95% CI = −0.37, −0.20; p < 0.001), but with significant heterogeneity. In either group, mean BCVA significantly improved following the implant (in the ERM group, MD = −0.31, 95% CI = −0.40, −0.22; in the RD group, MD = −0.22, 95% CI = −0.41, −0.03), with no difference between the two groups (p=0.41). However, there was significant heterogeneity in both groups. Considering the last available follow-up, a significant CMT reduction was found in the overall population, irrespective of the indication for vitrectomy (MD = −129.75, 95% CI = −157.49, −102.01; p < 0.001). In the ERM group, a significant CMT reduction was shown following DEX (MD = −133.41, 95% CI = −155.37, −111.45; p < 0.001), with no heterogeneity. In the RD group, mean CMT reduction was borderline significant (MD = −128.37, 95% CI = −253.57, −3.18; p=0.040), with significant heterogeneity. No difference in CMT improvement was found between the two groups (p=0.94). CONCLUSION: This meta-analysis showed that DEX yielded a significant improvement in visual and anatomical outcomes, even if limited by significant heterogeneity. Dexamethasone implant represents an effective treatment for postoperative macular oedema secondary to ERM and RD vitrectomy.